Fas/FasL promoter gene polymorphism in patients with rheumatoid arthritis - A. Berdeli; Ş. Kobak (Reumatismo, 2012)
Objectives. Fas/FasL is significantly involved in the pathogenesis of rheumatoid arthritis (RA). Fas/FasL gene polymorphism may be associated with susceptibility to rheumatoid arthritis and disease severity. Aim. To investigate the Fas 670 G/A and FasL 843 C/T genotype and allele frequency in patients with RA, and determine its potential association with susceptibility to the disease and the clinical parameters. Methods. One hundred and one patients with RA and 105 healthy control subjects were enrolled in the study. Fas 670 A/G and FasL 843C/T genotype polymorphism was investigated by PCR-RFLP. Chi-square test was used for determining the genotype distribution and the allele incidence. Results. There was no statistically significant difference between the patients with RA and the healthy subjects with respect to Fas-670 A/G and FasL-843C/T genotype distribution and allele frequency (P>0.05). While there was no statistically significant difference in disease severity and various clinical parameters, a correlation was detected between Fas-670 polymorphism and anti-CCP antibody and anemia (P<0.01 and P<0.03, respectively). Conclusions. Fas-670A/G and FasL-843C/T promoter gene polymorphisms are not considered to represent a major genetic risk factor for RA susceptibility and disease severity. However, based on these results, Fas-670 promoter polymorphism may modulate anti-CCP antibody synthesis and response in patients with rheumatoid arthritis.